Effects of irrigation and nitrogen on the performance of aerobic rice in northern China - Xue, Chang-Ying; Yang, Xiaoguang; Bouman, B.A.M.; Deng, Wei; Zhang, Qiu-Ping; Yang, Jie; Yan, Wei-Xiong; Zhang, Tianyi; Rouzi, A-Ji; Wang, Huaqi; Wang, Pu (Wiley, 2008)
Aerobic rice is a new production system in which specially‐developed varieties are grown under non‐flooded, non‐puddled, and non‐saturated soil conditions. In 2003–2004, irrigation x Nitrogen experiments were carried out near Beijing using variety HD297. Water treatments included four irrigation levels, and Nitrogen treatments included different fertilizer N application rates and different numbers of N splits. The highest yields were 4 460 kg/ha with 688 mm of total (rain plus irrigation) water input in 2003 and 6 026 kg/ha with 705 mm of water input in 2004. Because of the quite even distribution of rainfall in both years, the four irrigation treatments did not result in large differences of soil water conditions. There were few significant effects of irrigation on biomass accumulation, but yield increased with the total amount of water applied. High yields coincided with high harvest index and high percentages of grain filling. The application of fertilizer N either reduced biomass and yield or kept it at the same level as 0 N and consistently reduced the percentage grain filling and 1 000‐grain weight. With the highest water application, five splits of N gave higher yield than three splits, whereas three splits gave higher yield than five splits with lower water applications.